PEMANFAATAN SERAGAM KERJA SEBAGAI TEKS VISUAL DALAM PEMBELAJARAN LITERASI KRITIS SISWA SEKOLAH DASAR - Arfiani, Nanda Tiara; Ulfa, Syafrina; Apriani, Nur sakinah; Sihite, Yohantio Pantarihe (Universitas Negeri Medan, 2025)
Work uniforms are a form of visual text that is closely related to the everyday experiences of elementary school students and has the potential to be utilized as contextual learning media. This study aims to analyze Indomaret employee uniforms as a system of visual signs and to examine their potential as visual literacy media in Indonesian language learning at the elementary school level. The research employs a descriptive qualitative approach grounded in Charles Sanders Peirce’s semiotic theory, which includes icons, indexes, and symbols. The analysis focuses on the visual elements of the uniform, such as color, logos, clothing design, and accessories, as well as their relationship to the construction of meanings that can be understood by elementary school students. The findings indicate that Indomaret employee uniforms contain visual signs that are easily recognizable and relevant for use as instructional materials, particularly in descriptive text learning and in strengthening students’ ability to interpret symbolic meanings. Utilizing uniforms as contextual learning media can support the development of students’ visual literacy, critical thinking skills, and understanding of signs in everyday life. This study provides practical implications for elementary school teachers in designing Indonesian language instruction that is more meaningful, contextual, and oriented toward students’ real-life experiences.